High-performance cement-based repairing material and preparation method thereof
Through the combination of modified epoxy resin, synergistic curing agent and carbon nanotubes, a hyperbranched grid is formed, which solves the problem of high flowability but short settling time of cement-based repair materials, and significantly improves the mechanical properties and repair effects.
Patent Information
- Application Number
- CN202510084542.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-20
AI Technical Summary
At this stage, the flow rate of cement-based repair materials is too high but the settling time is short, and the mechanical properties after curing are poor, resulting in poor repair results.
Using modified epoxy resin and synergistic curing agent, a hyperbranched grid is formed by combining with carbon nanotubes and isooctyltriethoxysilane to enhance the mechanical properties of cement materials.
The balance between high flow and long settling time is achieved, while the mechanical properties of the repair materials are significantly improved and the repair effect is improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement-based repair material preparation, and in particular to a high-performance cement-based repair material and a preparation method thereof. Background Art
[0002] Since its advent, concrete materials have been widely used in various buildings and structures due to their excellent mechanical properties and good economy. Traditional cement-based materials are usually used in the main parts of buildings in engineering construction, such as tunnels, dams of water conservancy projects, and beams and columns of construction projects. The safety and stability of these projects are closely related to the normal life of the people. However, due to uneven settlement, stress concentration, and external erosion, the main structure of cement-based materials will have problems such as cracks, fractures, and skin peeling. In order to solve these problems, cement-based repair materials have come into being. Traditional cement-based repair materials have low fluidity and short setting time, and cannot fully fill cement gaps. In addition, the mechanical bite force with the repaired area is not high, and it will fall off after long-term use. In addition, the mechanical properties of the repaired cement-based materials are greatly reduced, resulting in poor repair effects. Summary of the invention
[0003] The purpose of the present invention is to provide a high-performance cement-based repair material and a preparation method thereof, which solves the problem that the cement-based repair material at the current stage has high fluidity but short setting time and poor mechanical properties after curing.
[0004] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a high-performance cement-based repair material comprises the following steps: Step A1: epoxy resin E-51 and polyethylene glycol are mixed, and trifluoroacetic acid is added under the conditions of a rotation speed of 120-150 r / min and a temperature of 120-125° C., and the mixture is stirred for 4-6 hours to obtain a water-based epoxy resin; water-based epoxy resin, n-decanoic acid, p-toluenesulfonic acid and DMF are mixed uniformly, and the mixture is reacted for 4-6 hours under the conditions of a rotation speed of 200-300 r / min and a temperature of 115-120° C. to obtain a modified epoxy resin; Step A2: mixing carbon nanotubes and mixed acid, reacting for 3-5 hours at a speed of 60-80 r / min and a temperature of 100-110° C., washing with deionized water until neutral to obtain carboxylated carbon nanotubes; mixing carboxylated carbon nanotubes, KH550, dicyclohexylcarbodiimide and toluene, reacting for 1-1.5 hours at a speed of 120-150 r / min and a temperature of 25-30° C., to obtain modified carbon nanotubes; Step A3: Weigh the following raw materials in parts by weight: 550-600 parts of cement, 650-700 parts of fly ash, 550-600 parts of quartz sand, 100-150 parts of modified epoxy resin, 350-400 parts of water and 6-8 parts of water reducer, mix them evenly to obtain component A, weigh the following raw materials in parts by weight: 10-20 parts of synergistic curing agent, 20-30 parts of modified carbon nanotubes and 5-10 parts of isooctyltriethoxysilane, mix them evenly to obtain component B, mix component A and component B evenly to obtain a high-performance cement-based repair material.
[0005] Furthermore, the molar ratio of the epoxy resin E-51 and polyethylene glycol described in step A1 is 2:1, the amount of trifluoroacetic acid used is 1.5‰ of the mass of the epoxy resin E-51, the molar ratio of the alcoholic hydroxyl group on the water-based epoxy resin and decanoic acid is 1:1, and the amount of p-toluenesulfonic acid used is 1% of the mass of decanoic acid.
[0006] Furthermore, the carbon nanotubes and the mixed acid in step A2 are used in a ratio of 1 g:80 mL, the mixed acid is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the molar ratio of the carboxyl groups on the carboxylated carbon nanotubes, KH550 and dicyclohexylcarbodiimide is 1:1:1.2.
[0007] Further, the synergistic curing agent is prepared by the following steps: Step B1: polyethylene glycol, p-formylbenzoic acid, 4-dimethylaminopyridine and toluene are mixed uniformly, and reacted at a speed of 120-150 r / min and a temperature of 115-120° C. for 2-3 hours to obtain intermediate 1; intermediate 1, ethylenediamine, p-toluenesulfonic acid and DMF are mixed, and reacted at a speed of 200-300 r / min and a temperature of 50-60° C. for 3-5 hours to obtain intermediate 2; Step B2: pentaerythritol, caffeic acid, 4-dimethylaminopyridine and toluene are mixed uniformly, and reacted at a speed of 120-150 r / min and a temperature of 115-120° C. for 3-5 hours to obtain intermediate 3; intermediate 3, 4-formylphenylboronic acid, tetraphenylpalladium, triethylamine and DMF are mixed uniformly, nitrogen is introduced for protection, and reacted at a speed of 60-80 r / min and a temperature of 60-80° C. for 10-15 hours to obtain intermediate 4; Step B3: Intermediate 2, intermediate 4, p-toluenesulfonic acid and DMF are mixed, and the reaction is carried out for 6-8 hours at a speed of 200-300 r / min and a temperature of 50-60° C. to obtain intermediate 5. Intermediate 5, mercaptoethanol, benzophenone and DMF are mixed evenly, and the reaction is carried out for 1-1.5 hours at a speed of 150-200 r / min, a temperature of 25-30° C. and irradiation with 365 nm ultraviolet light to obtain a synergistic curing agent.
[0008] Furthermore, the molar ratio of polyethylene glycol to p-formylbenzoic acid in step B1 is 1:2, the amount of 4-dimethylaminopyridine is 1% of the mass of p-hydroxybenzoic acid, and the molar ratio of intermediate 1 to ethylenediamine is 1:2.
[0009] Furthermore, the molar ratio of pentaerythritol to caffeic acid in step B2 is 1:4, the amount of 4-dimethylaminopyridine is 1% of the mass of caffeic acid, and the amount ratio of the intermediate 3,4-formylphenylboronic acid, tetraphenylpalladium and triethylamine is 1:1:0.01:1.5.
[0010] Furthermore, the molar ratio of intermediate 2 and intermediate 4 described in step B3 is 4:1, the amount of p-toluenesulfonic acid is 1.5% of the mass of intermediate 2, the molar ratio of the double bond on intermediate 5 and mercaptoethanol is 1:1, and the amount of benzophenone is 1‰ of the mass of mercaptoethanol.
[0011] Beneficial effects of the invention: A high-performance cement-based repair material disclosed by the invention comprises component A and component B, wherein component A comprises the following raw materials: cement, fly ash, quartz sand, modified epoxy resin, water and a water reducing agent, and component B comprises the following raw materials: a synergistic curing agent, modified carbon nanotubes and isooctyltriethoxysilane, wherein the modified epoxy resin is prepared by using epoxy resin E-51 and polyethylene glycol as raw materials, wherein under the action of trifluoroacetic acid, the epoxy group on the epoxy resin E-51 reacts with the hydroxyl group on the polyethylene glycol to prepare a water-based epoxy resin, wherein the water-based epoxy resin is esterified with n-decanoic acid so that the hydroxyl group on the side chain of the water-based epoxy resin reacts with the carboxyl group on the n-decanoic acid to prepare a modified epoxy resin, wherein the modified carbon nanotubes are treated with a mixed acid so that carboxyl groups are grafted onto the surface to prepare carboxylated carbon nanotubes, wherein the carboxylated carbon nanotubes are reacted with KH550 so that the carboxyl groups on the carboxylated carbon nanotubes react with the amino groups on the KH550 to prepare the modified carbon nanotubes.
[0012] The synergistic curing agent uses polyethylene glycol and p-formylbenzoic acid as raw materials, so that the hydroxyl group on the polyethylene glycol reacts with the carboxyl group on the p-formylbenzoic acid to obtain intermediate 1, the intermediate 1 is reacted with ethylenediamine, so that the aldehyde group on the intermediate 1 reacts with the amino group to form an amino end capping to obtain intermediate 2, pentaerythritol and caffeic acid are reacted, so that the hydroxyl group on the pentaerythritol reacts with the carboxyl group on the caffeic acid to obtain intermediate 3, the intermediate 3 is reacted with 4-formylphenylboronic acid, so that the catechol on the intermediate 3 reacts with the boric acid group on the 4-formylphenylboronic acid to obtain intermediate 4, the intermediate 2 is reacted with the intermediate 4, so that the amino group on the intermediate 2 reacts with the aldehyde group on the intermediate 4 to obtain intermediate 5, the intermediate 5 is reacted with mercaptoethanol, so that the double bond on the intermediate 5 reacts with the thiol group on the mercaptoethanol to obtain the synergistic curing agent.
[0013] When component A and component B are mixed and added to the cement material to be repaired, the modified epoxy resin, the synergistic curing agent and isooctyltriethoxysilane will flow into the gap, and the modified carbon nanotubes will also be embedded in the wider gap. Under the action of water, the isooctyltriethoxysilane and the siloxane on the modified carbon nanotubes are hydrolyzed to produce silanol groups that are mutually grafted, and are grafted with the hydroxyl groups on the side chains of the modified synergist and the hydroxyl groups on the surface of the cement material. The amino groups in the synergistic curing agent will react with the epoxy groups on the modified epoxy resin, and then solidify to produce stable filling in the gap. The side chains of the modified epoxy resin contain long-chain alkyl groups and the main chain to form a comb-like structure, while the synergistic curing agent is a hyperbranched structure. After reacting with the modified epoxy resin, a hyperbranched grid can be formed. The synergistic curing agent molecules contain dynamic crosslinking of borate and imide bonds, thereby enhancing the mechanical properties of the cement material. DETAILED DESCRIPTION
[0014] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0015] Embodiment 1: A method for preparing a high-performance cement-based repair material, comprising the following steps: Step A1: epoxy resin E-51 and polyethylene glycol are mixed, and trifluoroacetic acid is added under the conditions of a rotation speed of 120 r / min and a temperature of 120° C., and the mixture is reacted for 4 hours to obtain a water-based epoxy resin; water-based epoxy resin, n-decanoic acid, p-toluenesulfonic acid and DMF are mixed uniformly, and the mixture is reacted for 4 hours under the conditions of a rotation speed of 200 r / min and a temperature of 115° C. to obtain a modified epoxy resin; Step A2: mixing carbon nanotubes and mixed acid, reacting at a speed of 60 r / min and a temperature of 100° C. for 3 h, washing with deionized water until neutral to obtain carboxylated carbon nanotubes; mixing carboxylated carbon nanotubes, KH550, dicyclohexylcarbodiimide and toluene, reacting at a speed of 120 r / min and a temperature of 25° C. for 1 h to obtain modified carbon nanotubes; Step A3: Weigh the following raw materials in parts by weight: 550 parts of cement, 650 parts of fly ash, 550 parts of quartz sand, 100 parts of modified epoxy resin, 350 parts of water and 6 parts of water reducer, mix them evenly to obtain component A, weigh the following raw materials in parts by weight: 10 parts of synergistic curing agent, 20 parts of modified carbon nanotubes and 5 parts of isooctyltriethoxysilane, mix them evenly to obtain component B, mix component A and component B evenly to obtain a high-performance cement-based repair material.
[0016] The molar ratio of the epoxy resin E-51 and polyethylene glycol described in step A1 is 2:1, the amount of trifluoroacetic acid used is 1.5‰ of the mass of the epoxy resin E-51, the molecular weight of the polyethylene glycol is 1000, the molar ratio of the alcoholic hydroxyl group on the waterborne epoxy resin and n-decanoic acid is 1:1, and the amount of p-toluenesulfonic acid used is 1% of the mass of n-decanoic acid.
[0017] The amount ratio of the carbon nanotubes and the mixed acid described in step A2 is 1g:80mL, the mixed acid is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the molar ratio of the carboxyl group on the carboxylated carbon nanotubes, KH550 and dicyclohexylcarbodiimide is 1:1:1.2.
[0018] The cement described in step A3 is P•O42.5 cement, and the water reducing agent is polycarboxylic acid high-efficiency with a solid content of 30% and a water reducing efficiency of 35%.
[0019] The synergistic curing agent is prepared by the following steps: Step B1: polyethylene glycol, p-formylbenzoic acid, 4-dimethylaminopyridine and toluene are mixed uniformly, and reacted at a speed of 120 r / min and a temperature of 115° C. for 2 h to obtain intermediate 1; intermediate 1, ethylenediamine, p-toluenesulfonic acid and DMF are mixed, and reacted at a speed of 200 r / min and a temperature of 50° C. for 3 h to obtain intermediate 2; Step B2: pentaerythritol, caffeic acid, 4-dimethylaminopyridine and toluene were mixed uniformly, and the mixture was reacted at a speed of 120 r / min and a temperature of 115° C. for 3 h to obtain intermediate 3; intermediate 3, 4-formylphenylboronic acid, tetraphenylpalladium, triethylamine and DMF were mixed uniformly, nitrogen was introduced for protection, and the mixture was reacted at a speed of 60 r / min and a temperature of 60° C. for 10 h to obtain intermediate 4; Step B3: Intermediate 2, intermediate 4, p-toluenesulfonic acid and DMF are mixed, and the reaction is carried out at a speed of 200 r / min and a temperature of 50°C for 6 hours to obtain intermediate 5. Intermediate 5, mercaptoethanol, benzophenone and DMF are mixed evenly, and the reaction is carried out at a speed of 150 r / min, a temperature of 25°C and irradiation with 365 nm ultraviolet light for 1 hour to obtain a synergistic curing agent.
[0020] The molar ratio of polyethylene glycol to p-formylbenzoic acid in step B1 is 1:2, the amount of 4-dimethylaminopyridine is 1% of the mass of p-hydroxybenzoic acid, the molecular weight of polyethylene glycol is 1000, and the molar ratio of intermediate 1 to ethylenediamine is 1:2.
[0021] The molar ratio of pentaerythritol to caffeic acid in step B2 is 1:4, the amount of 4-dimethylaminopyridine is 1% of the mass of caffeic acid, and the amount ratio of the intermediate 3,4-formylphenylboronic acid, tetraphenylpalladium and triethylamine is 1:1:0.01:1.5.
[0022] The molar ratio of intermediate 2 and intermediate 4 described in step B3 is 4:1, the amount of p-toluenesulfonic acid used is 1.5% of the mass of intermediate 2, the molar ratio of the double bond on intermediate 5 and mercaptoethanol is 1:1, and the amount of benzophenone used is 1‰ of the mass of mercaptoethanol.
[0023] Embodiment 2: A method for preparing a high-performance cement-based repair material, comprising the following steps: Step A1: epoxy resin E-51 and polyethylene glycol are mixed, and trifluoroacetic acid is added under the conditions of a rotation speed of 120 r / min and a temperature of 125° C., and the mixture is reacted for 5 hours to obtain a water-based epoxy resin; water-based epoxy resin, n-decanoic acid, p-toluenesulfonic acid and DMF are mixed uniformly, and the mixture is reacted for 5 hours under the conditions of a rotation speed of 200 r / min and a temperature of 120° C. to obtain a modified epoxy resin; Step A2: mixing carbon nanotubes and mixed acid, reacting for 4 hours at a speed of 60 r / min and a temperature of 105° C., washing with deionized water until neutral to obtain carboxylated carbon nanotubes; mixing carboxylated carbon nanotubes, KH550, dicyclohexylcarbodiimide and toluene, reacting for 1.5 hours at a speed of 120 r / min and a temperature of 25° C., to obtain modified carbon nanotubes; Step A3: Weigh the following raw materials in parts by weight: 580 parts of cement, 680 parts of fly ash, 580 parts of quartz sand, 130 parts of modified epoxy resin, 380 parts of water and 7 parts of water reducer, mix them evenly to obtain component A, weigh the following raw materials in parts by weight: 15 parts of synergistic curing agent, 25 parts of modified carbon nanotubes and 8 parts of isooctyltriethoxysilane, mix them evenly to obtain component B, mix component A and component B evenly to obtain a high-performance cement-based repair material.
[0024] The molar ratio of the epoxy resin E-51 and polyethylene glycol described in step A1 is 2:1, the amount of trifluoroacetic acid used is 1.5‰ of the mass of the epoxy resin E-51, the molecular weight of the polyethylene glycol is 1000, the molar ratio of the alcoholic hydroxyl group on the waterborne epoxy resin and n-decanoic acid is 1:1, and the amount of p-toluenesulfonic acid used is 1% of the mass of n-decanoic acid.
[0025] The amount ratio of the carbon nanotubes and the mixed acid described in step A2 is 1g:80mL, the mixed acid is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the molar ratio of the carboxyl group on the carboxylated carbon nanotubes, KH550 and dicyclohexylcarbodiimide is 1:1:1.2.
[0026] The cement described in step A3 is P•O42.5 cement, and the water reducing agent is polycarboxylic acid high-efficiency with a solid content of 30% and a water reducing efficiency of 35%.
[0027] The synergistic curing agent is prepared by the following steps: Step B1: polyethylene glycol, p-formylbenzoic acid, 4-dimethylaminopyridine and toluene are mixed uniformly, and reacted at a speed of 120 r / min and a temperature of 120° C. for 2.5 h to obtain intermediate 1; intermediate 1, ethylenediamine, p-toluenesulfonic acid and DMF are mixed, and reacted at a speed of 200 r / min and a temperature of 55° C. for 4 h to obtain intermediate 2; Step B2: pentaerythritol, caffeic acid, 4-dimethylaminopyridine and toluene were mixed uniformly, and the mixture was reacted at a speed of 150 r / min and a temperature of 115° C. for 4 h to obtain intermediate 3; intermediate 3, 4-formylphenylboronic acid, tetraphenylpalladium, triethylamine and DMF were mixed uniformly, nitrogen was introduced for protection, and the mixture was reacted at a speed of 60 r / min and a temperature of 70° C. for 15 h to obtain intermediate 4; Step B3: Intermediate 2, intermediate 4, p-toluenesulfonic acid and DMF were mixed, and the reaction was carried out at a speed of 200 r / min and a temperature of 55°C for 7 hours to obtain intermediate 5. Intermediate 5, mercaptoethanol, benzophenone and DMF were mixed evenly, and the reaction was carried out at a speed of 150 r / min, a temperature of 30°C and irradiation with 365 nm ultraviolet light for 1.2 hours to obtain a synergistic curing agent.
[0028] The molar ratio of polyethylene glycol to p-formylbenzoic acid in step B1 is 1:2, the amount of 4-dimethylaminopyridine is 1% of the mass of p-hydroxybenzoic acid, the molecular weight of polyethylene glycol is 1000, and the molar ratio of intermediate 1 to ethylenediamine is 1:2.
[0029] The molar ratio of pentaerythritol to caffeic acid in step B2 is 1:4, the amount of 4-dimethylaminopyridine is 1% of the mass of caffeic acid, and the amount ratio of the intermediate 3,4-formylphenylboronic acid, tetraphenylpalladium and triethylamine is 1:1:0.01:1.5.
[0030] The molar ratio of intermediate 2 and intermediate 4 described in step B3 is 4:1, the amount of p-toluenesulfonic acid used is 1.5% of the mass of intermediate 2, the molar ratio of the double bond on intermediate 5 and mercaptoethanol is 1:1, and the amount of benzophenone used is 1‰ of the mass of mercaptoethanol.
[0031] Embodiment 3: A method for preparing a high-performance cement-based repair material, comprising the following steps: Step A1: epoxy resin E-51 and polyethylene glycol are mixed, and trifluoroacetic acid is added under the conditions of a rotation speed of 150 r / min and a temperature of 125° C., and the mixture is reacted for 6 hours to obtain a water-based epoxy resin; water-based epoxy resin, n-decanoic acid, p-toluenesulfonic acid and DMF are mixed uniformly, and the mixture is reacted for 6 hours under the conditions of a rotation speed of 300 r / min and a temperature of 120° C. to obtain a modified epoxy resin; Step A2: mixing carbon nanotubes and mixed acid, reacting for 5 hours at a speed of 80 r / min and a temperature of 110° C., washing with deionized water until neutral to obtain carboxylated carbon nanotubes; mixing carboxylated carbon nanotubes, KH550, dicyclohexylcarbodiimide and toluene, reacting for 1.5 hours at a speed of 150 r / min and a temperature of 30° C., to obtain modified carbon nanotubes; Step A3: Weigh the following raw materials in parts by weight: 600 parts of cement, 700 parts of fly ash, 600 parts of quartz sand, 150 parts of modified epoxy resin, 400 parts of water and 8 parts of water reducer, mix them evenly to obtain component A, weigh the following raw materials in parts by weight: 20 parts of synergistic curing agent, 30 parts of modified carbon nanotubes and 10 parts of isooctyltriethoxysilane, mix them evenly to obtain component B, mix component A and component B evenly to obtain a high-performance cement-based repair material.
[0032] The molar ratio of the epoxy resin E-51 and polyethylene glycol described in step A1 is 2:1, the amount of trifluoroacetic acid used is 1.5‰ of the mass of the epoxy resin E-51, the molecular weight of the polyethylene glycol is 1000, the molar ratio of the alcoholic hydroxyl group on the waterborne epoxy resin and n-decanoic acid is 1:1, and the amount of p-toluenesulfonic acid used is 1% of the mass of n-decanoic acid.
[0033] The amount ratio of the carbon nanotubes and the mixed acid described in step A2 is 1g:80mL, the mixed acid is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the molar ratio of the carboxyl group on the carboxylated carbon nanotubes, KH550 and dicyclohexylcarbodiimide is 1:1:1.2.
[0034] The cement described in step A3 is P•O42.5 cement, and the water reducing agent is polycarboxylic acid high-efficiency with a solid content of 30% and a water reducing efficiency of 35%.
[0035] The synergistic curing agent is prepared by the following steps: Step B1: polyethylene glycol, p-formylbenzoic acid, 4-dimethylaminopyridine and toluene are mixed uniformly, and reacted at a speed of 150 r / min and a temperature of 120° C. for 3 h to obtain intermediate 1; intermediate 1, ethylenediamine, p-toluenesulfonic acid and DMF are mixed, and reacted at a speed of 300 r / min and a temperature of 60° C. for 5 h to obtain intermediate 2; Step B2: pentaerythritol, caffeic acid, 4-dimethylaminopyridine and toluene were mixed uniformly, and the mixture was reacted at a speed of 150 r / min and a temperature of 120° C. for 5 h to obtain intermediate 3; intermediate 3, 4-formylphenylboronic acid, tetraphenylpalladium, triethylamine and DMF were mixed uniformly, nitrogen was introduced for protection, and the mixture was reacted at a speed of 80 r / min and a temperature of 80° C. for 15 h to obtain intermediate 4; Step B3: Intermediate 2, intermediate 4, p-toluenesulfonic acid and DMF are mixed, and the reaction is carried out at a speed of 300 r / min and a temperature of 60°C for 8 hours to obtain intermediate 5. Intermediate 5, mercaptoethanol, benzophenone and DMF are mixed evenly, and the reaction is carried out at a speed of 200 r / min, a temperature of 30°C and irradiation with 365nm ultraviolet light for 1-1.5 hours to obtain a synergistic curing agent.
[0036] The molar ratio of polyethylene glycol to p-formylbenzoic acid in step B1 is 1:2, the amount of 4-dimethylaminopyridine is 1% of the mass of p-hydroxybenzoic acid, the molecular weight of polyethylene glycol is 1000, and the molar ratio of intermediate 1 to ethylenediamine is 1:2.
[0037] The molar ratio of pentaerythritol to caffeic acid in step B2 is 1:4, the amount of 4-dimethylaminopyridine is 1% of the mass of caffeic acid, and the amount ratio of the intermediate 3,4-formylphenylboronic acid, tetraphenylpalladium and triethylamine is 1:1:0.01:1.5.
[0038] The molar ratio of intermediate 2 and intermediate 4 described in step B3 is 4:1, the amount of p-toluenesulfonic acid used is 1.5% of the mass of intermediate 2, the molar ratio of the double bond on intermediate 5 and mercaptoethanol is 1:1, and the amount of benzophenone used is 1‰ of the mass of mercaptoethanol.
[0039] Comparative Example 1: Compared with Example 1, this comparative example uses carbon nanotubes instead of modified carbon nanotubes, and the other steps are the same.
[0040] Comparative Example 2: Compared with Example 1, this comparative example uses aqueous epoxy resin instead of modified epoxy resin, and the remaining steps are the same.
[0041] Comparative Example 3: Compared with Example 1, ethylene glycol is used instead of pentaerythritol in this comparative example, and the other steps are the same.
[0042] Comparative Example 4: Compared with Example 1, this comparative example uses intermediate 5 instead of the synergistic curing agent, and the remaining steps are the same.
[0043] The cement-based repair materials prepared in Examples 1-3 and Comparative Examples 1-4 were tested for fluidity according to the standard of JC / T1083-2008, tested for setting time according to the standard of GB / T1346-2011, and made into 40mm×40mm×160mm specimens according to the standard of GB / T17671-2021 to test the compressive strength. The test results are shown in Table 1 below.
[0044]
[0045] It can be seen from the above table that the present application has excellent fluidity, a long setting time, and better mechanical properties.
[0046] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a high-performance cement-based repair material, characterized in that: The specific steps include: Step A1: epoxy resin E-51 and polyethylene glycol are mixed and stirred, and trifluoroacetic acid is added to react to obtain a water-based epoxy resin; the water-based epoxy resin, n-decanoic acid, p-toluenesulfonic acid and DMF are mixed and reacted to obtain a modified epoxy resin; Step A2: After the carbon nanotubes and the mixed acid are mixed and reacted, the mixture is washed with deionized water until it is neutral to obtain carboxylated carbon nanotubes, and the carboxylated carbon nanotubes, KH550, dicyclohexylcarbodiimide and toluene are mixed and reacted to obtain modified carbon nanotubes; Step A3: Weigh the following raw materials in parts by weight: 550-600 parts of cement, 650-700 parts of fly ash, 550-600 parts of quartz sand, 100-150 parts of modified epoxy resin, 350-400 parts of water and 6-8 parts of water reducer, mix them evenly to obtain component A, weigh the following raw materials in parts by weight: 10-20 parts of synergistic curing agent, 20-30 parts of modified carbon nanotubes and 5-10 parts of isooctyltriethoxysilane, mix them evenly to obtain component B, mix component A and component B evenly to obtain a high-performance cement-based repair material.
2. The method for preparing a high-performance cement-based repair material according to claim 1, characterized in that: The molar ratio of the epoxy resin E-51 and polyethylene glycol described in step A1 is 2:1, and the molar ratio of the alcoholic hydroxyl group on the waterborne epoxy resin and n-decanoic acid is 1:
1.
3. The method for preparing a high-performance cement-based repair material according to claim 1, characterized in that: The amount ratio of the carbon nanotubes and the mixed acid described in step A2 is 1g:80mL, the mixed acid is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the molar ratio of the carboxyl group on the carboxylated carbon nanotubes, KH550 and dicyclohexylcarbodiimide is 1:1:1.
2.
4. The method for preparing a high-performance cement-based repair material according to claim 1, characterized in that: The synergistic curing agent is prepared by the following steps: Step B1: polyethylene glycol, p-formylbenzoic acid, 4-dimethylaminopyridine and toluene are mixed and reacted to obtain intermediate 1, and intermediate 1, ethylenediamine, p-toluenesulfonic acid and DMF are mixed and reacted to obtain intermediate 2; Step B2: Pentaerythritol, caffeic acid, 4-dimethylaminopyridine and toluene are mixed to react to obtain intermediate 3, and intermediate 3, 4-formylphenylboronic acid, tetraphenylpalladium, triethylamine and DMF are mixed evenly, and nitrogen is introduced for protection to react to obtain intermediate 4; Step B3: Intermediate 2, intermediate 4, p-toluenesulfonic acid and DMF are mixed and reacted to obtain intermediate 5, and intermediate 5, mercaptoethanol, benzophenone and DMF are mixed and reacted to obtain a synergistic curing agent.
5. The method for preparing a high-performance cement-based repair material according to claim 4, characterized in that: The molar ratio of polyethylene glycol to p-formylbenzoic acid in step B1 is 1:2, and the molar ratio of intermediate 1 to ethylenediamine is 1:
2.
6. The method for preparing a high-performance cement-based repair material according to claim 4, characterized in that: The molar ratio of pentaerythritol to caffeic acid in step B2 is 1:4, and the usage ratio of the intermediate 3,4-formylphenylboronic acid, tetraphenylpalladium and triethylamine is 1:1:0.01:1.
5.
7. The method for preparing a high-performance cement-based repair material according to claim 4, characterized in that: The molar ratio of intermediate 2 to intermediate 4 in step B3 is 4:1, and the molar ratio of the double bond on intermediate 5 to mercaptoethanol is 1:
1.
8. A high-performance cement-based repair material, characterized in that: Prepared according to any one of claims 1 to 7.
Citation Information
Patent Citations
High-toughness epoxy resin adhesive and preparation method thereof
CN118792005A
Cardanol-blocked polyisocyanate emulsion, preparation method thereof and application of cardanol-blocked polyisocyanate emulsion in waterproof finishing of fabric
CN118792880A
Epoxy resin composition for repairing of spalling of concrete pavement
KR101454753B1
Eco-Friendly New Material Paint Film for Treatment of Concrete Structure and Constructing Methods Thereof
KR101791932B1
Aquatic hardening mortar composition and repair-reinforcement method using the same
KR102218635B1